-Practice before Practicum: Simulation in Initial Teacher Education. Issue 2 (8th April 2022) - Fischetti, John; Ledger, Susan; Lynch, Debra; Donnelly, Debra
Abstract: The benefits of micro-teaching (pre-service teachers practicing their teaching skills with small groups of peers or students) are well documented. However, the overcrowding of the teacher education curriculum, in part due to regulatory mandates, led many initial teacher education (ITE) programs to abandon using micro-teaching. The focus of this study was to understand the experiences of pre-service teachers who are engaging in real-time simulation technology as a new form of micro-teaching. The analysis of our findings indicated that the use of the mixed-reality learning environments (MRLEs) showed promise in helping build candidate self-confidence and preparing novices for their first "real" teaching practicum. MRLEs appear to be particularly useful for assisting with developing confidence, planning for diverse learners, understanding personalizing pedagogy and engaging with classroom management. We argue the importance of micro-teaching "2.0" as a strategy to "practice before prac" and call for increased inclusion of simulation within ITE programs.